Design of Direct Current Microgrid Converter with Cost-Effective Low-Voltage Battery Storage System - Juraj Tvarožek; Michal Prazenica; Tomáš Paulec; Slavomir Kaščák; Patrik Resutík (Applied Sciences)
Battery storage systems are becoming very popular around the world. However, they are mainly used in industry for high-performance applications. Domestic use is still sporadic due to size and cost issues. This work overviews basic conceptual designs for a cost-effective battery storage system. The main specificity of the proposed systems is the use of commonly available recycled batteries from household appliances such as laptops and backup power supplies. The circuit topology considered is a 3S (three cells in series) configuration. This is because such wiring arrangements are those that are most often found in the home appliances described here. The technical solutions of the device itself focus on the ratio of the efficiency of the whole system to the production cost. Given the above, attention was paid to the simulation analysis of the operating modes, which directly influenced the components’ price. Changing the switching control scheme of the power transistors makes it possible to reduce the requirements for the driving components used with minimal impact on the power conversion efficiency (Δη 1–4%). According to the established findings, a prototype was made on which the simulation findings were verified; then, we further focused on the experimental measurement of the efficiency of the MPPT converter and conducted an analysis of a methodology in which we measure the deviation from the actual point of maximum power. The simple possibility of parallelizing the individual storage devices will again help improve the system’s overall efficiency. This makes the system suitable for use in small spaces such as houses, garages, cellars, etc.